2021
DOI: 10.1002/ajpa.24410
|View full text |Cite
|
Sign up to set email alerts
|

Muscle attachment sites and behavioral reconstruction: An experimental test of muscle‐bone structural response to habitual activity

Abstract: Objective Behavioral reconstruction from muscle attachment sites (entheses) is a common practice in anthropology. However, experimental evidence provides mixed support for the assumed association between enthesis size and shape with changes in habitual activity. In this study, a laboratory mouse model was used to experimentally test whether activity level and type alters muscle architecture and the underlying bone cross‐sectional geometry of entheses in order to assess the underlying assumption that behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Living bone can functionally adapt 1 to loads it experiences and thus reflects, to some extent, the behaviour of individuals over their lifetime. This functional adaptation, caused by modelling and remodelling of bone 2 , has been experimentally demonstrated in external shape change 1 , 3 , the thickening of cortical bone 1 , 4 , entheseal shape change on the cortical bone surface 5 , 6 , and change in the architecture of trabecular bone 7 , 8 , or a combination of these phenomena. Unlike cortical bone, trabecular architecture is usually completely internal, concentrated in the epiphyses of long bones, and far more porous at the mesoscale 9 .…”
Section: Introductionmentioning
confidence: 92%
“…Living bone can functionally adapt 1 to loads it experiences and thus reflects, to some extent, the behaviour of individuals over their lifetime. This functional adaptation, caused by modelling and remodelling of bone 2 , has been experimentally demonstrated in external shape change 1 , 3 , the thickening of cortical bone 1 , 4 , entheseal shape change on the cortical bone surface 5 , 6 , and change in the architecture of trabecular bone 7 , 8 , or a combination of these phenomena. Unlike cortical bone, trabecular architecture is usually completely internal, concentrated in the epiphyses of long bones, and far more porous at the mesoscale 9 .…”
Section: Introductionmentioning
confidence: 92%
“…After approximately 9 weeks of being housed in one of the two environments, all remaining animals were euthanized and their skeletons were cleaned by dermestid action and stored for future analyses. The use of mice that were aged approximately 3 to 12 weeks during the experimental period is ideal for investigating the effects of physical activity on entheseal morphology, as the entheses of mice (like those of humans) are likely most sensitive to mechanical loading during the growth period (Turcotte et al, 2022).…”
Section: Experiments and Samplementioning
confidence: 99%
“…Although the in vivo activity of the muscles attaching to the four entheses studied has not been measured in mice during climbing, indirect evidence suggests that climbing generally engenderers relatively greater activation of at least some of the muscles. In particular, young mice experimentally treated with climbing exercise were shown to develop hypertrophic deltoid muscles (attaching to the deltoid tuberosity) and rotator cuff muscles (variably attaching to the greater and lesser tubercles) compared to non‐exercised mice engaged solely in quadrupedal activity on a cage floor (Green et al, 2012; Rabey et al, 2015; Turcotte et al, 2022). In addition, forelimb supination involving the supinator muscle (attaching to the supinator crest) has been shown to be a key component of the mouse forelimb reaching, grasping, and retraction cycle (do Couto Nicola et al, 2022), suggesting that the supinator muscle might also require greater activation during climbing.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple validation studies have generated evidence that it is not yet possible to reconstruct any aspect of muscle anatomy from the surface morphology of a single enthesis (e.g., Karakostis, Wallace, et al, 2019; Rabey et al, 2015; Williams‐Hatala et al, 2016; Zumwalt, 2006, contra Karakostis et al, 2021) and two notable studies demonstrated that presumed entheseal surface morphology (e.g., a bony crest) is at times present in areas where the associated muscle does not actually attach (Marzke et al, 2007) or where there is no muscle at all (Eliot & Jungers, 2000). However, internal entheseal morphology may be more informative of behaviors when recorded from juvenile individuals (Turcotte et al, 2022). Another promising line of research has demonstrated that groups of entheses can be used to separate individuals into behavioral groups (e.g., occupation, walking patterns) on the basis of muscle synergies (e.g., Karakostis & Lorenzo, 2016; Karakostis, Wallace, et al, 2019; Karakostis, Jeffery, & Harvati, 2019).…”
Section: Part 3: Evolutionmentioning
confidence: 99%